Understanding brand reputation and customer loyalty through online customer service VS offline customer service in X Solutions Limited - Kader, Syed Mashriqul (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.